The Relationship between Mathematics Anxiety and Mathematical Performance among Undergraduate Students - Zanabazar, Altanchimeg; Deleg, Amartuvshin; Ravdan, Magsar; Tsogt-erdene, Enguunmurun (Jurnal Ilmiah Peuradeun, 2023)
Mathematics has become imperative for citizens of the new millennium, as it has become crucial for self-managed life activities. Still, the perception that "mathematics is a difficult subject" hinders students from handling the subject seriously. This type of phobia limits the students’ opportunity to select professions and study in prospective fields to guarantee a smooth career in the future. The purpose of this study was to determine how student mathematics anxiety affects student mathematics achievement. The sample for the survey was selected randomly. We proposed the hypothesis that “the levels of mathematical anxiety have a negative impact on mathematical performance”. Consequently, descriptive, correlation, and regression analyses have been carried out to prove our hypothesis. We used the Mathematics Anxiety Rating Scale questionnaire (A-MARS) developed by Richardson and Suinn (1972) for assessing mathematics anxiety and the General Entrance Exam (GEE) results in mathematics are considered the achievement criteria. The study’s results illustrated the negative linear correlation (r = -0.479, p <0.05) between mathematics anxiety and mathematical performance. In another world, the results show that mathematics anxiety negatively affects students' mathematical performance.